Researchers Use Software to Find Chip Flaws. (Computer (00189162), 2008)
The article reports on the development of a software that has the ability identify problems in chips and recommends a possible fix by scientists at the University of Michigan. The software would benefit software manufacturers as it will aid them in coping with the growing number of bugs that take time to fix as chips become more complex. According to Valeria Bertacco, a university assistant professor working on the software, processors now house a number of transistors and perform a growing number of functions. This could lead to more bugs which makes it difficult and time-consuming to identify them before vendors ship the chips.